2021
DOI: 10.1017/s0967199421000320
|View full text |Cite
|
Sign up to set email alerts
|

Review of Sertoli cell dysfunction caused by COVID-19 that could affect male fertility

Abstract: Spermatogenesis is a complex and elaborate differentiation process and is vital for male fertility. Sertoli cells play a major role in fertility and induce spermatogenesis by protecting, nourishing, and supporting germ cells. It has been speculated that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could directly affect the male reproductive system, and therefore heredity and fertility. The similarity of SARS-CoV-2 to SARS-CoV could confirm this hypothesis because both viruses use angiotensin-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…However, FSH serum level was insignificantly higher compared with the controls, which could be due to Leydig and Sertoli cell dysfunction 38 . Tabar et al shown how the ACE2-mediated pathway may be used by SARS-CoV-2 infection to harm Sertoli cells and trigger the onset of male infertility 39 . Moreover, other endocrinopathies in LC patients, such as thyroid dysfunction and insulin resistance, may cause functional hypogonadotropic hypogonadism 12 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, FSH serum level was insignificantly higher compared with the controls, which could be due to Leydig and Sertoli cell dysfunction 38 . Tabar et al shown how the ACE2-mediated pathway may be used by SARS-CoV-2 infection to harm Sertoli cells and trigger the onset of male infertility 39 . Moreover, other endocrinopathies in LC patients, such as thyroid dysfunction and insulin resistance, may cause functional hypogonadotropic hypogonadism 12 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronologically, spermatogonia stages are either undifferentiated A-type or differentiating. GSCs are undifferentiated A single (As) spermatogonia [1,2]. Daughter cells formed from undifferentiated As (A single ) spermatogonia in mice may move to direct stem cell renewal or give rise to additional undifferentiated A-type spermatogonia, which go through differentiation stages.…”
Section: Introductionmentioning
confidence: 99%